Analysis of publications relating giftedness, creativity and bilingualism in the scielo, scopus and web of science databases - Ferreira, Taís Crema Remoli [UNESP]; Chacon, Miguel Claudio Moriel [UNESP]; Capellini, Vera Lucia Messias Fialho [UNESP] (FapUNIFESP (SciELO), 2021)
In this article, it was proposed to conduct a search in a national database (SciELO) and in two international ones (Scopus and Web of Science), in order to investigate possible connections between the themes giftedness, creativity and bilingualism, as interest in the three terms has been growing. In the verification carried out in 2020 with different combinations of these uniterms, written in Portuguese and English, no work related to the three topics was found, but ten articles addressing the connection between two of the topics were obtained. The connection between giftedness and bilingualism was the most recurrent theme, with six studies. Most of them investigated how to evaluate and work with gifted bilingual students inserted in different realities with the authors’ criticism of the standardized evaluations and tests that were not concerned with encompassing cultural and linguistic differences in these instruments. The four other articles addressed creativity and bilingualism and were focused on comparing different measures of creativity of bilingual and monolingual children. Through the data obtained in the texts, there was a more significant gain in different measures of creativity for bilingual children. From the analysis of the findings, there was little production related to the themes presented, even though the search was limited to the connection of only two of the aforementioned uniterms. Thus, new studies are suggested in bilingual environments with a focus on target students of Special Education, specifically those with giftedness. It is also recommended the development of creativity in this context and the dissemination of more empirical research so that new works can be replicated.
Análise de publicações relacionando altas habilidades/ superdotação, criatividade e bilinguismo nas bases de dados scielo, scopus e web of science
Keywords: Bilingualism; Creativity; Giftedness; Literature review; Special Education